Religion, sexual ethics, and the politics of belonging: Young Muslims and Christians in the Netherlands. (March 2020) - Beekers, Daan; Schrijvers, Lieke L
This article offers a comparative study of everyday sexual ethics among Dutch Sunni Muslim and evangelical Christian young adults, both those born into religious families and those converted later in life. In European public debates, the sexual values of observant Christians and – especially – observant Muslims, are commonly understood to deviate from progressive norms. Particularly for Muslims, this has become a ground for questioning their belonging to the moral nation. Our ethnographic analysis complicates these conventional representations, which are partly reflected in quantitative survey research. We argue that the sexual ethics of the young Muslims and Christians we studied are multi-layered, situational, and dialogical. Discussing the convergences and divergences between these groups, we point to a paradox: while Muslims tend to be set apart as sexually 'other', the young Christians we worked with – and to a lesser extent the converted Muslims – put strikingly more effort into distinguishing themselves from, and criticising, dominant sexual norms.